Comparative effects of ethylene inhibitors on Agrobacterium-mediated transformation of drought-tolerant wild watermelon. Issue 3 (4th March 2018) - Malambane, Goitseone; Nonaka, Satoko; Shiba, Hiroshi; Ezura, Hiroshi; Tsujimoto, Hisashi; Akashi, Kinya
Abstract: Ethylene (C2 H4 ), a phytohormone that is produced in response to both abiotic and biotic stresses, is an important factor influencing the efficiency of Agrobacterium -mediated transformation. In this study, effects of various ethylene inhibitors on the efficiency of Agrobacterium -mediated genetic transformation in drought-tolerant wild watermelon was comparatively examined. Consequently, in comparison to the application of chemical inhibitors such as AgNO3 and aminoethoxyvinylglycine (AVG), lower ethylene level was observed when the infecting Agrobacterium contained a gene for 1-aminocyclopropane-carboxylic acid (ACC) deaminase ( acdS ), which cleaves ethylene precursor ACC into α-ketobutyrate and ammonia. GUS histochemical and spectrophotometric enzyme assays showed that acdS was more effective in enhancing gene transfer than the chemical ethylene inhibitors. Efficiency of transgenic shoots formation was higher in acdS - and AVG-treated explants. These observations demonstrated that controlling the ethylene level during co-cultivation and shoot formation, particularly using the acdS -harboring Agrobacterium, is advantageous for enhancing the transformation efficiency in this plant. Abstract: : A gene for 1-aminicyclopropane-carboxylic acid deaminase was effective for enhancing the efficiency of genetic transformation in wild watermelon.